Neck pain: global epidemiology, trends and risk factors - Kazeminasab, Somaye; Nejadghaderi, Seyed Aria; Amiri, Parastoo; Pourfathi, Hojjat; Araj-Khodaei, Mostafa; Sullman, Mark J. M.; Kolahi, Ali-Asghar; Safiri, Saeid (BMC musculoskeletal disorders, 2022)
Background Neck pain is one of the most common musculoskeletal disorders, having an age-standardised prevalence rate of 27.0 per 1000 population in 2019. This literature review describes the global epidemiology and trends associated with neck pain, before exploring the psychological and biological risk factors associated with the initiation and progression of neck pain. Methods The PubMed database and Google Scholar search engine were searched up to May 21, 2021. Studies were included that used human subjects and evaluated the effects of biological or psychological factors on the occurrence or progression of neck pain, or reported its epidemiology. Results Psychological risk factors, such as long-term stress, lack of social support, anxiety, and depression are important risk factors for neck pain. In terms of the biological risks, neck pain might occur as a consequence of certain diseases, such as neuromusculoskeletal disorders or autoimmune diseases. There is also evidence that demographic characteristics, such as age and sex, can influence the prevalence and development of neck pain, although further research is needed. Conclusions The findings of the present study provide a comprehensive and informative overview that should be useful for the prevention, diagnosis, and management of neck pain.